Auger electron spectroscopy characterization of Ti/NiV/Ag multilayer back-metal for monitoring of Ni migration on Ag surface. Issue 9 (August 2015) - Ricciari, R.; Ferlito, E.P.; Pizzo, G.; Padalino, M.; Anastasi, G.; Sacchi, M.; Pappalardo, G.; Consalvo, C.; Mello, D.
Abstract: In the semiconductor manufacturing process an important issue is the process control, not only on the front end device processes, but also for back finish steps. The backside metallization is usually done by a multilayer metallic film on the back Si surface, of which the characteristics are strongly related to the assembly process and the reliability of the device. In this work we have investigated a suitable way to monitor Ni migration on Ti/NiV/Ag back metallization layer, using the Auger electron spectroscopy (AES) analytical technique. It is known that Ni migration on Ag surface is a cause of bonding failures, as voids in the solder or detachments, because the oxidation of Ni inhibits proper metallurgical bonding. The multilayer has been characterized using AES, atomic force microscopy (AFM) and transmission electron microscopy (TEM) analyses, before and after thermal processes (130 °C, 5 h) in order to emphasize the eventual Ni migration on the surface. Afterwards, the procedure to monitor this critical step using AES was fixed. Highlights: Capability of Auger analysis to detect low concentration of contaminants element. Nickel migration on surface is very well observable. The possibility to have a precise chemical map of the surface, is shown Well results were found in a specific DOEcreated to simulate the thermal stress conditions The purpose is to use AES in order to fix a method to detect and study the problems of die attach imputable to Ni migration.